INVESTIGATION ON THE VIBRATIONAL SPECTRA AND GEOMETRY OF FLUAZINAM: A DFT MODUS (International Journal of Food and Nutritional Sciences, 2022)
The designated compound has been inspected through quantum chemical computations andthe geometry of which is optimized to minimum energy configuration by B3LYP/6-311 ++ G (d, p) basisset employing DFT approach. Electron transfer from donor to acceptor orbitals has been analysed throughNatural bond Orbital (NBO) analysis .Vibrational modes were assigned based on Potential EnergyDistribution (PED) contribution. In the optimized geometry, C-N bond length displays a double bond naturedue to the transfer of lone pair electron from amide group nitrogen to the pyridine ring which is also justifiedin the natural bond analysis.